The significance of magnetized thermal radiation on the magnetohydrodynamic (MHD) behavior of Williamson hybrid ferrofluids over a stretching sheet - D. Thenmozhi; M. Eswara Rao; P.D. Selvi; RLV. Renuka Devi; S. Kiranmaiye; Ch. Nagalakshmi (International Journal of Thermofluids)
The goal of this study is to investigate the fluid dynamics of a pseudoplastic Williamson nanofluid model, explicitly focusing on blood infused with magnetite (Fe2O3) and (Cu) copper nanoparticles, with the aim of enhancing its physiological and industrial applications. This research offers a novel approach by integrating the Williamson fluid model with magnetic nanoparticles, which has not been widely explored in biomedical applications like antitumor therapy and magnetic hyperthermia. The study is mathematically modeled using partial differential equations (PDEs) accounting for the deformation vortices of a stretching surface. These governing equations are transformed into ordinary differential equations (ODEs) via similarity transformations and solved numerically using the Runge-Kutta (R-K) 4th-order method coupled with the shooting technique. The velocity and temperature fields are then analyzed through MATLAB simulations. Results indicate that increasing the Williamson, radiation, and nanoparticle volume fraction parameters elevates the fluid temperature, whereas higher magnetic field strength, Prandtl number, and stretching parameter values reduce it. The novelty of this work lies in its application of the Williamson nanofluid model to real-time medical applications, such as cancer treatment through magnetic hyperthermia, and its potential use in advanced biomedical devices.